The Legal Liability of State-Owned Enterprise Directors for Corporate Losses: Balancing the Business Judgment Rule and Unlawful Acts - Samuel Sitompul; Anwar Budiman; Uyan Wiryadi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This research is motivated by legal issues in determining the limit of liability of the directors of State-Owned Enterprises (SOEs) when a business decision causes losses. The main problem lies in the difficulty of distinguishing between reasonable business risks and unlawful acts, as well as the lack of optimal application of the Business Judgment Rule doctrine as legal protection for directors. This complexity is increasing because SOEs have a dual position as business entities as well as separate state wealth managers, so SOEs' losses are often associated as state losses and have the potential to criminalize the business policies of the board of directors. Although previous research has partially examined this issue, there has been no study that systematically integrates the analysis of the legal liability limit with the application of the Business Judgment Rule in the context of the dualism of the public and private legal regime in SOEs. This study uses normative legal methods with legislative, conceptual, and case approaches, as well as primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that the liability of the board of directors cannot be determined only based on the existence of losses, but must be proven that there are irregularities such as errors, negligence, abuse of authority, conflicts of interest, or bad faith. The Business Judgment Rule can be applied as legal protection as long as the decision is taken in good faith, based on adequate information, without conflict of interest, and in the interests of the company. This study offers an integrative analytical framework that affirms the Business Judgment Rule as a balancing mechanism between the protection of business discretion and legal accountability in the management of SOEs.